Warm-feeling hot air nonwoven fabric, preparation method and application thereof

By impregnating the oxidized yttrium alginate solution with ES fiber hot air nonwoven fabric and spraying the mixed solution of polyvinylpyrrolidone, zirconium carbide and dopamine, a multi-layer network structure is formed, which solves the problem of difficult temperature control and hardening of the existing warm sanitary products, and achieves good softness and warm sensation performance.

CN117569094BActive Publication Date: 2025-03-25XIANGYANG YINGLE SANITARY PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311560618.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-20
Publication Date
2025-03-25
Estimated Expiration
2043-11-20

AI Technical Summary

Technical Problem

Among existing warm sanitary products, the temperature of the heat patch is difficult to control, which may cause body burns. At the same time, the internal material of the heat patch becomes hard after the heat reaction, reducing the comfort of the sanitary products.

Method used

By immersing the ES fiber hot air nonwoven fabric in the oxidized sodium alginate solution and spraying the aqueous dispersion mixture of polyvinylpyrrolidone, zirconium carbide and dopamine, a multi-layer network structure is formed to improve the softness of the material and the adhesion of the coating layer, and adjustable temperature range.

Benefits of technology

This method improves the softness of the non-woven fabric and the adhesion of the coating layer, avoids the problem of hardening and brittleness of the material, and at the same time enhances the adhesion of zirconium carbide, improves the warmth performance and the stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004563471560000051
    Figure BDA0004563471560000051
  • Figure BDA0004563471560000061
    Figure BDA0004563471560000061
Patent Text Reader

Abstract

The invention discloses a warm-feeling hot-air nonwoven fabric, a preparation method and application thereof. The preparation steps of the warm-feeling hot-air nonwoven fabric include: immersing the ES fiber hot-air nonwoven fabric in an oxidized sodium alginate solution and then taking it out; spraying a water-dispersed mixed solution of polyvinyl pyrrolidone, zirconium carbide and dopamine onto the immersed ES fiber hot-air nonwoven fabric, and drying the mixed solution after standing at room temperature to obtain the warm-feeling hot-air nonwoven fabric; the preparation method can enable the material to form a multi-layer network structure inside and on the surface of the nonwoven fabric through self-assembly and cross-linking, which can effectively improve the adhesion of the material to zirconium carbide, avoid the zirconium carbide from falling off, and increase the loading amount of zirconium carbide and the stability of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sanitary products, in particular to warm-feeling hot-air nonwoven fabrics, and a preparation method and application thereof. Background Art

[0002] Hot air nonwoven fabrics are widely used in disposable sanitary products such as baby diapers and sanitary napkins. Warm sanitary products can effectively prevent babies from getting various diseases caused by cold stomachs and waists; reduce dysmenorrhea caused by cold uterus, warm uterus and protect abdomen. Therefore, the development of warm hot air nonwoven fabrics is of great significance.

[0003] In the prior art, the heating effect of heating patches is usually used to achieve a warming effect. However, the temperature of heating patches is generally difficult to control, which may cause problems such as body burns. At the same time, the internal material of the heating patch becomes hard after the thermal reaction, which will reduce the comfort of sanitary products. Therefore, it is very meaningful to develop a warm-feeling hot air non-woven fabric that has good softness, strong coating adhesion, and an adjustable temperature change range. Summary of the invention

[0004] The present invention provides a method for preparing a warm-feeling hot-air nonwoven fabric, which is used to take into account softness, strong coating layer adhesion and warm-feeling performance, and improve the performance of the nonwoven fabric used in sanitary products.

[0005] In view of this, the scheme of the present invention is:

[0006] The first aspect of the present invention provides a method for preparing a warm air nonwoven fabric, the steps comprising:

[0007] The ES fiber hot air nonwoven fabric is immersed in the oxidized sodium alginate solution and then taken out;

[0008] The aqueous dispersion mixture of polyvinyl pyrrolidone, zirconium carbide and dopamine was sprayed onto the impregnated ES fiber hot air nonwoven fabric, and then dried after standing at room temperature to obtain the warm hot air nonwoven fabric.

[0009] Furthermore, the mass ratio of zirconium carbide, polyvinyl pyrrolidone and deionized water in the water-dispersed mixed liquid is 1:(1-4):(20-40).

[0010] Furthermore, the concentration of dopamine in the water-dispersed mixed solution is 0.1-10 g / L.

[0011] Furthermore, after spraying, 2 The spraying amount of zirconium carbide on the non-woven fabric is 1.25 to 5 mg.

[0012] Optionally, the molecular weight of the polyvinyl pyrrolidone ranges from 58,000 to 1,300,000.

[0013] Optionally, the particle size of the zirconium carbide is 50nm to 1000nm.

[0014] Furthermore, the oxidized sodium alginate solution is prepared by mixing a sodium alginate solution with sodium periodate.

[0015] Furthermore, the concentration of the oxidized sodium alginate solution is 0.5 to 5 mg / mL; and the immersion time is 0.5 to 2 hours.

[0016] Furthermore, the room temperature standing time is 1 to 4 hours; and the drying temperature is 40 to 80°C.

[0017] The second aspect of the present invention provides a warm-feeling hot air nonwoven fabric obtained by the above-mentioned preparation method.

[0018] The third aspect of the present invention provides a sanitary product, comprising the warm-feeling hot air nonwoven fabric described in the second aspect.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The preparation method of the warm-feeling non-woven fabric provided by the present invention is to pre-impregnate the ES fiber hot air non-woven fabric with loaded oxidized sodium alginate, so that the inside and surface of the inert non-woven fabric have aldehyde reaction sites, and at the same time improve the bonding ability of the inside and surface of the non-woven fabric, avoid the disadvantage of the common surface cross-linking reaction that the cross-linked material becomes hard and brittle, and spray polyvinyl pyrrolidone to further make the material have good softness, which can be applied to sanitary products. The amide bond on the polyvinyl pyrrolidone can form a hydrogen bond with the hydroxyl group on the dopamine. At the same time, the cross-linking reaction between the aldehyde group on the oxidized sodium alginate and the amino group on the dopamine allows the material to form a multi-layer network structure through self-assembly and cross-linking inside and on the surface of the non-woven fabric, which can effectively improve the adhesion of the material to zirconium carbide, avoid the shedding of zirconium carbide, and increase the loading amount of zirconium carbide and the stability of the material.

[0021] 2. The present invention adopts a spraying method to prepare the warm-feeling hot air nonwoven fabric, which is simple to prepare and can be produced continuously. The warm-feeling hot air nonwoven fabric contains zirconium carbide nanoparticles with light-absorbing properties, which can produce a warm feeling under the irradiation of infrared light, meet the requirements of the warm feeling performance, and is suitable for sanitary products. DETAILED DESCRIPTION

[0022] The technical solution of the present invention will be clearly and completely described below in conjunction with the preferred embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The following is a preferred experimental example for preparing a warm-feeling hot air nonwoven fabric. Except for the method specifically defined in the text, the means involved in the process are means mastered by those skilled in the art, and the reagents used are all commercially available industrial standard products.

[0024] Example 1

[0025] Select ES fiber hot air non-woven fabric with a size of 10cm*10cm and a gram weight of 25g per square meter. Mix the sodium alginate solution with sodium periodate to prepare a 1mg / mL oxidized sodium alginate solution, then immerse the ES fiber hot air non-woven fabric in the above oxidized sodium alginate solution for 2 hours and take it out. Dissolve 0.5g of polyvinyl pyrrolidone with a molecular weight of 130000 in 5mL of deionized water, add 0.25g of zirconium carbide powder with a particle size of 50nm and 5mg of dopamine, stir and mix evenly, and then spray the mixture evenly onto the above ES fiber hot air non-woven fabric loaded with oxidized sodium alginate through a spray gun. After standing at room temperature for 1 hour, the sprayed non-woven fabric is dried at 60°C for 2 hours to obtain a warm hot air non-woven fabric.

[0026] Example 2

[0027] Select ES fiber hot air non-woven fabric with a size of 10cm*10cm and a gram weight of 25g per square meter. Mix the sodium alginate solution with sodium periodate to prepare a 3mg / mL oxidized sodium alginate solution, then immerse the ES fiber hot air non-woven fabric in the above oxidized sodium alginate solution for 1 hour and take it out. Dissolve 0.25g of polyvinyl pyrrolidone with a molecular weight of 58000 in 5mL of deionized water, add 0.125g of zirconium carbide powder with a particle size of 800nm ​​and 50mg of dopamine, stir and mix evenly, and then spray the mixture evenly onto the above ES fiber hot air non-woven fabric loaded with oxidized sodium alginate through a spray gun. After standing at room temperature for 2 hours, the sprayed non-woven fabric is dried at 80°C for 1 hour to obtain a warm hot air non-woven fabric.

[0028] Example 3

[0029] Select ES fiber hot air non-woven fabric with a size of 10cm*10cm and a gram weight of 25g per square meter. Mix the sodium alginate solution with sodium periodate to prepare a 5mg / mL oxidized sodium alginate solution, then immerse the ES fiber hot air non-woven fabric in the above oxidized sodium alginate solution for 0.5h and take it out. Dissolve 0.5g of polyvinyl pyrrolidone with a molecular weight of 130000 in 5mL of deionized water, add 0.125g of zirconium carbide powder with a particle size of 50nm and 2mg of dopamine, stir and mix evenly, and then spray the mixture evenly onto the above ES fiber hot air non-woven fabric loaded with oxidized sodium alginate through a spray gun. After standing at room temperature for 1 hour, the sprayed non-woven fabric is dried at 60°C for 2 hours to obtain a warm hot air non-woven fabric.

[0030] Comparative Example 1 (Non-oxidized Sodium Alginate)

[0031] Select ES fiber hot air non-woven fabric with a size of 10cm*10cm and a gram weight of 25g per square meter, dissolve 0.5g of polyvinyl pyrrolidone with a molecular weight of 130000 in 5mL of deionized water, add 0.25g of zirconium carbide powder with a particle size of 50nm and 5mg of dopamine, stir and mix evenly, and then use a spray gun to evenly spray the mixture onto the above-mentioned ES fiber hot air non-woven fabric. After standing at room temperature for 1 hour, the sprayed non-woven fabric is dried at 60°C for 2 hours to obtain a warm hot air non-woven fabric.

[0032] Comparative Example 2 (without dopamine)

[0033] Select ES fiber hot air nonwoven fabric with a size of 10cm*10cm and a gram weight of 25g per square meter, mix the sodium alginate solution with sodium periodate to prepare a 1mg / mL oxidized sodium alginate solution, and then immerse the ES fiber hot air nonwoven fabric in the above oxidized sodium alginate solution for 2 hours and take it out. Dissolve 0.5g of polyvinyl pyrrolidone with a molecular weight of 130000 in 5ml of deionized water, add 0.25g of zirconium carbide powder with a particle size of 50nm, stir and mix evenly, and spray the mixture onto the ES fiber hot air nonwoven fabric through a spray gun. After standing at room temperature for 1 hour, the sprayed nonwoven fabric is dried at 60°C for 2 hours to obtain a warm hot air nonwoven fabric.

[0034] Comparative Example 3 (without polyvinyl pyrrolidone)

[0035] Select ES fiber hot air non-woven fabric with a size of 10cm*10cm and a gram weight of 25g per square meter. Mix the sodium alginate solution with sodium periodate to prepare a 1mg / mL oxidized sodium alginate solution, then immerse the ES fiber hot air non-woven fabric in the above oxidized sodium alginate solution for 2 hours and take it out. Add 0.25g of zirconium carbide powder with a particle size of 50nm and 5mg of dopamine to 5 ml of deionized water, stir and mix evenly, and then spray the mixture evenly onto the above ES fiber hot air non-woven fabric loaded with oxidized sodium alginate through a spray gun. After standing at room temperature for 1 hour, the sprayed non-woven fabric is dried at 60°C for 2 hours to obtain a warm hot air non-woven fabric.

[0036] Experimental example

[0037] 1. Temperature Sensing Experiment

[0038] The nonwoven fabrics prepared in Examples 1 to 3 and Comparative Examples 1 to 3, as well as the untreated ES nonwoven fabric, were irradiated with a 150W infrared lamp to detect the increase in surface temperature relative to the original temperature. The results are shown in Table 1.

[0039] Table 1:

[0040]

[0041] The results show that the temperature of Examples 1 to 3 can be increased by more than 22°C within 2 minutes, and can be increased by more than 26°C after 10 minutes. However, the temperature of Comparative Examples 1 to 3 only increased by 14°C within 2 minutes, and increased by 20°C within 10 minutes. In comparison, the temperature sensing performance is significantly reduced compared with Examples 1 to 3. The possible reason is that due to the zirconium carbide loading rate, Examples 1 to 3 first impregnate oxidized sodium alginate, so that the inside and surface of the inert non-woven fabric have aldehyde reaction sites, which improves the binding ability of the non-woven fabric, and then loads polyvinyl pyrrolidone, dopamine and zirconium carbide by spraying. The cross-linking reaction between the aldehyde group on the oxidized sodium alginate and the amino group on the dopamine, and the hydrogen bonding between the amide bond on the polyvinyl pyrrolidone and the hydroxyl group on the dopamine, make the material form a multi-layer network structure through self-assembly and cross-linking inside and on the surface of the non-woven fabric, which can effectively strengthen the adhesion of the material to zirconium carbide, and increase the loading amount of zirconium carbide and the stability of the material.

[0042] 2. Zirconium carbide loading rate detection

[0043] The test results of zirconium carbide loading rates of the non-woven fabrics prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 2.

[0044] Table 2:

[0045]

[0046] It is not difficult to see from Table 2 that the zirconium carbide loading rate of the warm-feeling hot air non-woven fabrics prepared in Examples 1 to 3 is significantly higher than that of Comparative Examples 1 to 3. Compared with Example 1, Comparative Example 1 does not impregnate oxidized sodium alginate, resulting in no aldehyde reaction sites inside and on the surface of the non-woven fabric, and the binding ability of the non-woven fabric decreases. In addition, it cannot undergo a cross-linking reaction with the amino group on dopamine; Compared with Example 1, Comparative Example 2 does not add dopamine, resulting in a lack of groups that can cross-link with the aldehyde groups of oxidized sodium alginate, and the cross-linking reaction is weakened; Comparative Example 3 does not add polyvinyl pyrrolidone, lacks amide bonds that can form hydrogen bonds with the hydroxyl groups on dopamine, and the hydrogen bonding effect is weakened, which will affect the formation of a multi-layer network structure on the surface and inside of the non-woven fabric, resulting in a decrease in the bonding force and binding force of zirconium carbide, thereby affecting the loading rate.

[0047] 3. Non-woven fabric softness test

[0048] The softness test results of the nonwoven fabrics prepared in Examples 1 to 3 are shown in Table 3.

[0049] Table 3:

[0050] Softness Example 1 Example 2 Example 3 Blank ES nonwoven fabric Transverse softness (g) 1.7 1.9 1.8 1.6 Longitudinal softness (g) 1.2 1.3 1.2 1.1

[0051] From the results in Table 3, it can be seen that the softness of the ES nonwoven fabric is not significantly changed by first dipping in the oxidized sodium alginate solution and then spraying the ES nonwoven fabric in Examples 1 to 3, which meets the softness requirements of the product.

[0052] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a warm-feeling hot air nonwoven fabric, characterized in that the steps include: The ES fiber hot air nonwoven fabric is immersed in the oxidized sodium alginate solution and then taken out; Spraying a water-dispersed mixture of polyvinyl pyrrolidone, zirconium carbide and dopamine onto the impregnated ES fiber hot air nonwoven fabric, leaving it to stand at room temperature and then drying it to obtain a warm hot air nonwoven fabric; The mass ratio of zirconium carbide, polyvinyl pyrrolidone and deionized water in the aqueous dispersion mixture is 1: (1-4): (20-40); The concentration of dopamine in the water-dispersed mixed solution is 0.1-10 g / L.

2. The preparation method according to claim 1, characterized in that: After spraying, per cm 2 The spraying amount of zirconium carbide on the non-woven fabric is 1.25~5mg.

3. The preparation method according to claim 1, characterized in that: The molecular weight of the polyvinyl pyrrolidone is in the range of 58,000 to 1,300,000; and / or the particle size of the zirconium carbide is in the range of 50 nm to 1,000 nm.

4. The preparation method according to claim 1, characterized in that: The oxidized sodium alginate solution is prepared by mixing a sodium alginate solution with sodium periodate.

5. The preparation method according to claim 1, characterized in that: The concentration of the oxidized sodium alginate solution is 0.5-5 mg / mL; and / or the immersion time is 0.5-2 h.

6. The preparation method according to claim 1, characterized in that: The room temperature standing time is 1-4 hours; and / or the drying temperature is 40-80°C.

7. The warm air nonwoven fabric obtained by the preparation method according to any one of claims 1 to 6.

8. A sanitary product, characterized in that: The invention comprises the warm air nonwoven fabric as claimed in claim 7.

Citation Information

Patent Citations

  • Oxidized sodium alginate modified textile fiber as well as preparation method and application thereof

    CN103243557A

  • Hydroxybutyl chitosan / oxidized sodium alginate / nano-silver composite hydrogel dressing plaster

    CN105107008A